Contemporary Management of Jugular Paragangliomas With Neural Preservation. (February 2021) - Manzoor, Nauman F.; Yancey, Kristen L.; Aulino, Joseph M.; Sherry, Alexander D.; Khattab, Mohamed H.; Cmelak, Anthony; Morrel, William G.; Haynes, David S.; Bennett, Marc L.; O'Malley, Matthew R.; Netterville, James; Wanna, George; et al.
Objectives: Management of jugular paragangliomas (PGL) has evolved toward subtotal resection (STR). The purpose of this study is to analyze neural preservation and adjuvant treatment for long-term local control. Study Design: Retrospective chart review. Settings: Tertiary neurotology practice. Subjects and Methods: Adults undergoing surgical treatment of jugular PGL between 2006 and 2019. Patients, disease, and treatment variables were collected retrospectively. Single predictor logistic regression was used to ascertain predictors of regrowth or need for salvage radiation. Results: A total of 41 patients (median age, 47 years; 76% female) were identified. Most patients presented with advanced-stage disease (Glasscock-Jackson stage III-IV = 76%). Subtotal resection (STR) was performed in 32 (78%) patients. Extended STR (type 1) was the most commonly performed conservative procedure (n = 19, 59%). Postoperative new low cranial neuropathy (LCN) involving CN X and XII was rare (n = 3 and n = 1, respectively). Seventeen patients (41%) underwent postsurgical therapy for tumor regrowth or recurrence, including 15 patients who underwent adjuvant (n = 4) or salvage (n = 11) radiation. Overall tumor control of 94.7% was achieved at a mean follow-up of 35 months. All patients treated with combined modality treatment had local control at last follow-up. Logistic regression identified no single predictor for postsurgical radiation treatment or salvage-free survival. Conclusion: Management of jugular PGL with a conservative approach is safe and effective with a low rate of new LCN deficit. Active surveillance of residual tumor with salvage radiation for growth results in excellent long-term tumor control.